THEORETICAL REFLECTIONS ON INTERNATIONAL JUSTICE: FACING HEDLEY BULL - Ana Paula Tostes; Marcelo Mello Valença (Revista Eletrônica do Curso de Direito da UFSM, 2017)
The article aims to introduce a reflection on the impact of Grotian rationalism in the debate on international justice. The challenge of achieving a common justice among sovereign states permeates classical debates of history and theories about the constitution of international society in the post-war period. This is a theoretical research that seeks to deepen the debate on justice and introduce a dialogue between authors from different fields of study that have not been confronted in an interdisciplinary environment that allows the deepening of concepts of justice for researchers of international legal and political topics. The main argument is that the theoretical contribution of Hedley Bull, to face the possible contradictions between order and justice values in the international anarchy, contributes to the debate on the concepts and limits of an international justice. The article is divided into three parts. The first part focuses on the combination of Bull’s reflections with the theoretical debates about justice. The second part presents a consideration on the subjectivity of international justice. The third part stretches the conceptual problems of justice under the relativity argument prism of priorities and goals to be achieved. The conclusion guides the final consideration on the importance of the contribution of a rational perspective that seeks to merge the prevalence of legal equality and sovereignty of states with the possible threat of the order. Getting unfinished the subject of exploitation by its very nature, the article seeks to contribute to a interdisciplinary insight into the arrangement of the characteristics of society and anarchy of the international order at the same time, and the advantages of a minimum order under the rational point of view.